Android-based Al-qur'an application development and culture "Nggahi Mbojo" - Arifin Arifin; Hidayat Hidayat; Asmedy Asmedy; Andi Prayudi; Fathirma'ruf Fathirma'ruf (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
To overcome AL-Qur'an illiteracy in TPQ students can us the Qiroati method, Iqro`, An Nahdliyah, Yanbu`a, and Tartili, but are not very effective. The learning model applied by Al-Qur`an teachers is currently less attractive because they are still using the old method they are used to learning to use "Nggahi Mbojo" in every Qur'an learning, this study aims to produce the Qur'an, The Android-Based Application and Local Culture “Nggahi Mbojo” is of good quality with valid, practical and effective criteria. This research is a development research (Development Research) by developing learning tools that include, Al-Qur'an Learning Applications and IQRO Reading Ability Assessment Instruments, this research procedure refers to the 4-D model (Four D model) which is carried out on TPQ Santri total 40 people, in Pajo District, Dompu Regency in 2022, Data analysis in this study uses quantitative data analysis, through analysis of the validity of the device by experts, practicality analysis and analysis of the effectiveness of the device seen from student learning outcomes, the results of the analysis show that the learning tools used are of good quality with categories Valid, Practically effective for use in the process learning to read the Koran for students.